Analysis on Architectural Aesthetic Dimensions of the Temple of the Dawn Complex. Issue 1 (September 2020) - Wu, Tong; Guo, Yakun
Abstract: The multi-ethnic indigenous culture, the inclusive Indian religious form and the political concept of the unity of god and king provide the unique aesthetic connotation and humanistic spirit for the development of religious architectural art in Thailand. From the perspective of design aesthetics, this paper intends to analyze the aesthetic dimensions and style characteristics of the Temple of the Dawn Complex, from the three aspects of "Essence", "Form" and "Content" through field research, combining with literature materials. It explores the cultural symbiosis presented by the diversified features and influencing factors of the decorations in the Temple of the Dawn Complex in Thailand.